EFEKTIVITAS METODE LATIHAN FUN GAMES TERHADAP HASIL BELAJAR TEKNIK SMASH SEPAK TAKRAW - Katsran Zallaf (PRODI PJKR UNIVERSITAS MUHAMMADIYAH MUARA BUNGO, 2021)
ABSTRACT The purpose of this study was to see the effect of fun games training on the learning outcomes of the sepak takraw smash technique for the students of SMA Negeri 1 Sutera, Pesisir Selatan Regency. This type of research is experimental (quasi-experimental) which aims to see the effect of treatment on variables. The treatment in this research is fun games exercise. The population in this study amounted to 11 people. The sampling technique used proportional sampling. Thus the number of samples in this study were 11 students of SMA Negeri 1 Sutera, Pesisir Selatan Regency. The data analysis technique used is t test analysis (mean difference test) with a significant level of = 0.05. The results showed that the average score of the pre-test was 13 and the average score after the post-test was 17. Based on the t-test, the value of tcount = 5.177> ttable = 2.23, with a confidence level of = 0.05. The results showed that there was a significant effect of the fun games training method on the learning outcomes of the sepak takraw smash technique for the students of SMA Negeri 1 Sutera, Pesisir Selatan Regency. This means that one of the training methods, namely fun games, can be used to influence the learning outcomes of the sepak takraw smash technique. Keywords: Fun Games, Smash, Sepak Takraw